BORN-INFELD ELECTRODYNAMICS and EULER-HEISENBERG-LIKE MODEL: OUTSTANDING EXAMPLES of THE LACK of COMMUTATIVITY AMONG QUANTIZED TRUNCATED ACTIONS and TRUNCATED QUANTIZED ACTIONS - Accioly, Antonio Jose [UNESP]; Gaete, Patricio; Helayel-Neto, Jose A. (World Scientific Publ Co Pte Ltd, 2010)
We calculate the lowest-order corrections to the static potential for both the generalized Born-Infeld electrodynamics and an Euler-Heisenberg-like model, in the presence of a constant external magnetic field. Our analysis is carried out within the framework of the gauge-invariant but path-dependent variables formalism. The calculation reveals a long-range correction (1/r(5)-type) to the Coulomb potential for the generalized Born-Infeld electrodynamics. Interestingly enough, in the Euler-Heisenberg-like model, the static potential remains Coulombian. Therefore, contrary to popular belief, the quantized truncated action and the truncated quantized action do not commute at all.
Keywords: Euler-Heisenberg-like model; Born-Infeld theory; static potential